ς(B) Activity Depends on RsbU in Staphylococcus aureus - Giachino, P. (American Society for Microbiology, 2001)
Derivatives of the widely used laboratory strain Staphylococcus aureus NCTC8325, which are natural rsbU mutants, were shown to be unable to produce RsbU, a positive regulator of the alternative sigma factor ς(B). The lack of RsbU prevented the heat-dependent production of ς(B)-controlled transcripts and resulted in reduced H(2)O(2) and UV tolerance, enhanced alpha-hemolysin activity, and the inability to produce the alkaline shock protein Asp23. After 48 h of growth, rsbU mutant strains failed to accumulate staphyloxanthin, the major stationary-phase carotenoid. Transcription of Asp23 was found to be exclusively controlled by ς(B), making it an excellent target for the study of ς(B) activity in S. aureus. Reporter gene experiments, using the firefly luciferase gene (luc+) fused to the ς(B)-dependent promoter(s) of asp23, revealed that ς(B) is almost inactive in 8325 derivatives. cis complementation of the 8325 derivative BB255 with the wild-type rsbU gene from strain COL produced the rsbU(+) derivative GP268, a strain possessing a ς(B) activity profile comparable to that of the rsbU(+) wild-type strain Newman. In GP268, the heat inducibility of ς(B)-dependent genes, Asp23 production, alpha-hemolysin activity, pigmentation, and susceptibility to H(2)O(2) were restored to the levels observed in strain Newman, clearly demonstrating that RsbU is needed for activation of ς(B) in S. aureus.